2020
DOI: 10.3390/app10031189
|View full text |Cite
|
Sign up to set email alerts
|

Laser Irradiation Effects at Different Wavelengths on Phenology and Yield Components of Pretreated Maize Seed

Abstract: This study aims to compare the effects of different laser wavelengths, exposure times, and low-power-intensity laser irradiation on maize seeds. Seeds were exposed to He–Ne (632.8 nm) red laser, Nd:YAG second-harmonic-generation (532 nm) green laser, and diode (410 nm) blue laser. Four different exposure times (45, 65, 85, and 105 s) with different intensity (2 and 4 mW/cm2), for each laser were tested. Phenology and yield components (plant height, leaf area, number of rows per ear, seed yield, harvest index, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…Obtaining a high crop yield requires high-quality seeds that can produce rapid and uniform seedling emergence ( Hernandez-Aguilar, Dominguez-Pacheco & Cruz-Orea, 2015 ). Seed vigor is the physiological quality that related to rapid, uniform seedling emergence, and development under different soil conditions ( Hasan et al, 2020a ; Hasan et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obtaining a high crop yield requires high-quality seeds that can produce rapid and uniform seedling emergence ( Hernandez-Aguilar, Dominguez-Pacheco & Cruz-Orea, 2015 ). Seed vigor is the physiological quality that related to rapid, uniform seedling emergence, and development under different soil conditions ( Hasan et al, 2020a ; Hasan et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…To this aim, laser light has been particularly useful, owing to its specific characteristics ( Hernandez-Aguilar et al, 2009 ). Existing studies suggested a positive influence of pre-sowing seed exposure to laser beams on the induction of seed germination, initial seed development, and yield of selected seeds ( Chen et al, 2005 ; Ćwintal, Dziwulska-Hunek & Wilczek, 2010 ; Hasan et al, 2020a ; Li et al, 2013 ; Podlesna et al, 2015 ). However, little is known about the mechanism through which laser beams influence seeds and plants because few studies address it ( Álvarez et al, 2011 ; Hernandez-Aguilar, Dominguez-Pacheco & Cruz-Orea, 2015 ; Podlesna et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cadmium is one of the most harmful non-essential heavy metals that, regardless of its quantity, affects plants in a detrimental way by triggering severe disorders in plant functionality and structure [ 15 ]. In plant stress physiology, there is an increasing need for stress detection technologies with the help of which the physiological state of plants can be characterised with particular attention to non-invasiveness [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural sustainability and food security are a priority not only within the European policy framework, but also on a global scale. Interest in the use of lasers in agriculture has existed for some time [1], but in recent years this technology has experienced a real renaissance, indeed, for some it is seen as the only correct way to produce healthy, high-quality food [2]. Laser technology is mainly used for pre-sown seed exposure in order to achieve better and faster germination in various, often unfavourable, habitat conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Laser technology is mainly used for pre-sown seed exposure in order to achieve better and faster germination in various, often unfavourable, habitat conditions. The scientific literature has confirmed that it has various bio-stimulation effects (positive, negative, neutral), which are conditioned by the physical parameters of the laser, including radiation dose and exposure time, and the selection of plant material [2][3][4]. The inappropriate selection of physical parameters for the plant material may cause unwanted mutagenic effects [5,6].…”
Section: Introductionmentioning
confidence: 99%